IMPLEMENTASI PROGRAM LITERASI SISWA DALAM MENINGKATKAN GEMAR MEMBACA DI KELAS IV SDN 2 PASIRLAWANG KABUPATEN CIAMIS - Suciati, Ati; Hidayat, Yusuf; Sugiarti, Sri (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
Literacy program is an activity to increase students’ interest in reading. The study aims to determine the implementation and impact of literacy program to increase the reading enthusiasm at 4th grade students of SDN 2 Pasirlawang, Ciamis Regency. This study used a qualitative method under a case study. The results of the study showed that the literacy program at 4th grade students of SDN 2 Pasirlawang, Ciamis Regency was implemented well and effectively, at which the program was able to foster the students' reading habits, train students' analysis, and students' understanding in writing. In addition, the implementation of literacy program at 4th grade students of SDN 2 Pasirlawang, Ciamis Regency had an impact on: (1) increasing students' enthusiasm to read; (2) increasing students' ability to analyze and summarize reading into journal; (3) increasing students' skill in writing and critical thinking; (4) increasing students’ pleasure in participating literacy activities at school.